2008
DOI: 10.3200/jach.56.6.601-606
|View full text |Cite
|
Sign up to set email alerts
|

Licit and Illicit Use of Medications for Attention-Deficit Hyperactivity Disorder in Undergraduate College Students

Abstract: Drug use was associated with a lower GPA in ADHD-diagnosed students than in students without ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
105
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 21 publications
3
105
0
3
Order By: Relevance
“…The increase in stimulant prescriptions has resulted in a corresponding escalation of illicit use, particularly in college students, confirmed by numerous survey results (Advokat et al, 2008;Arria & DuPont, 2010;Hall et al, 2005;McCabe et al, 2005;Rabiner et al, 2008;2009a, 2009bRabiner et al, 2010;Teter et al, 2003;Teter et al, 2005;Teter et al, 2006;Weyandt et al, 2009;White et al, 2006;Wilens et al, 2008). Wilens and colleagues (2008) report lifetime rates of diversion ranging from 16 to 29%, with medical prescriptions being given, sold or traded by students.…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…The increase in stimulant prescriptions has resulted in a corresponding escalation of illicit use, particularly in college students, confirmed by numerous survey results (Advokat et al, 2008;Arria & DuPont, 2010;Hall et al, 2005;McCabe et al, 2005;Rabiner et al, 2008;2009a, 2009bRabiner et al, 2010;Teter et al, 2003;Teter et al, 2005;Teter et al, 2006;Weyandt et al, 2009;White et al, 2006;Wilens et al, 2008). Wilens and colleagues (2008) report lifetime rates of diversion ranging from 16 to 29%, with medical prescriptions being given, sold or traded by students.…”
mentioning
confidence: 85%
“…Some (Advokat et al, 2008;Blase et al, 2009) have found significantly lower GPAs in ADHDdiagnosed college students relative to non-ADHD controls. Not surprisingly, higher levels of ADHD symptomatology are consistently associated with poor study habits, skills and academic adjustment, and greater self-reports of attention deficits (Norwalk et al, 2009;Schwanz et al, 2007).…”
Section: Academic Achievement Of College Students With Adhdmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Many researchers believe that the rise in students with ADHD is due to the use of stimulants taken to increase their academic performance. 8 It is noted through previous research that students with ADHD are at risk of experiencing emotional difficulties, dropping out of school and likely to underperform in the classroom setting; more so these students tend to have lower Grade Point Averages (GPA) and more likely to be placed on academic probation. 9 For many students, sports serve as a natural remedy for ADHD and the symptoms associated with the mental disorder.…”
Section: Managing the Student-athlete With Adhdmentioning
confidence: 99%